Survival Trends in Sorafenib for Advanced Hepatocellular Carcinoma: A Reconstructed Individual Patient Data Meta-analysis of Randomized Trials - Darren Jun Hao Tan; Ansel Shao Pin Tang; Wen Hui Lim; Cheng Han Ng; Benjamin Nah; Clarissa Fu; Jieling Xiao; Benjamin Koh; Phoebe Wen Lin Tay; Eunice X Tan; Margaret Teng; Nicholas Syn; et al. (Liver Cancer, 2023)
Background: Emerging data suggest that outcomes for advanced hepatocellular carcinoma (HCC) treated with sorafenib may have improved over time. We aimed to provide robust, time-to-event estimates of survival outcomes for sorafenib in advanced HCC.